Body in the bathhouse - Davis, Lindsey (New York : Mysterious Press, 2002)
Ancient Roman investigator Marcus Didius Falco finds trouble on the site of a new palace being built by the king of the Atrebtes tribe in distant Britain
"A Marcus Didius Falco mystery novel"--Jacket.
85389
Keywords: Falco, Marcus Didius (Fictitious character) -- Fiction; Private investigators -- Rome -- Fiction; Romans -- Great Britain -- Fiction; Great Britain -- History -- Roman period, 55 B.C.-449 A.D. -- Fiction; Rome -- History -- Vespasian, 69-79 -- Fiction; Historical fiction; Mystery fiction